PENGEMBANGAN KURIKULUM PENDIDIKAN KARAKTER DI MADRASAH BERBASIS KURIKULUM MERDEKA - Ikhwanul Muslimin (Institut Agama Islam Darussalam Blokagung, 2023)
This study examines the development of the character education curriculum in Madrasahs with reference to the Merdeka curriculum. The concept of the Merdeka curriculum is expected to be able to produce students who are knowledgeable, characterized, civilized, and noble according to the noble ideals of the Indonesian nation. Madrasahs as educational institutions must implement character education in the Merdeka curriculum with the concept of its Pancasila learner profile. The approach used in this research uses qualitative with the literature study method, researchers use several books, journals, and the results of recent observations as references. The findings reveal that the development of character education carried out in learning must be integrated into each subject, self-development, and Madrasah culture. Character values developed in students can be through two attitudes, namely spiritual and social. Spiritual is carrying out the teachings of the religion they adhere to, while social includes honest behavior, discipline, responsibility, courtesy, environmental care, and confidence in interacting with the environment. Some stages of learner character development can be passed through 1) knowledge, 2) implementation, and 3) habits.